Obstetrical and Neonatal Outcome of Pregnancies Complicated with SARS-CoV-2 Infection - Diana Cristina SECARA; Madalina Daniela IORDACHE; Ana Veronica UZUNOV; Octavian MUNTEANU; Alexandru BAROS; Monica Mihaela CIRSTOIU (Modern Medicine)
COVID-19 pandemic had an impact without precedent. Pregnant women are part of the vulnerable population and the extent of SARS-CoV-2 infection consequences on obstetrical and neonatal outcome are still studied. It’s been speculated, based on what is known about other pathogenic viruses, SARS-CoV-2 virus can interfere with placental defense mechanisms and increase the miscarriage and preterm birth rate. Often, pregnant women infected with SARS-CoV-2 virus develop mild pneumonia. Severe pneumonia occurs very rarely and is statistically significant related to neonatal death. Our study has been conducted in a multidisciplinary hospital unit and included 184 pregnant women with SARS-COV-2 infection who gave birth in our hospital, diagnosed through polymerase chain reaction. There have been analyzed data regarding the maternal symptomatology, the gestational age, the method of giving birth, complications that have occurred during birth, the newborns weight and neonatal outcome through Apgar score. There have been three cases of severe infection with maternal death and one case with neonatal death. Overall, 20% of patients had mild symptomatology, 2% had severe form and the rest of the patients were asymptomatic. We found a high rate of preterm birth and intrauterine growth restriction and an increase incidence of acute fetal distress followed by caesarean section. SARS-CoV-2 virus affects both the mother and the fetus as a whole and, subsequently, individually. Our results show the adverse obstetrical and neonatal outcome in peripartum period complicated with SARS-CoV-2 infection even in asymptomatic and mild-symptomatic cases.